Medication Adherence and its Association with Treatment Satisfaction and Diabetes Related Psychological Distress among Type 2 Diabetes Mellitus Patients: A Cross-sectional Study from Rural Thiruvallur District, India - PL Thameen Raja Mohamed; AH Irfaunul Azees; Vinodhini Balamurugan; S Shravan Kumar; Ruma Dutta (Journal of Clinical and Diagnostic Research)
Introduction: Effective management of Type 2 Diabetes Mellitus (T2DM) requires sustained medication adherence. However non adherence coupled with low treatment satisfaction and psychological distress, can adversely impact glycaemic control. Aim: To assess the level of medication adherence among patients with T2DM, and also to determine its relationship between treatment satisfaction, diabetes-related psychological stress. Materials and Methods: A community based cross-sectional study was conducted at ACS Medical College and Hospital, Thiruvallur, Tamil Nadu, India, from January to April 2024 among 350 adult T2DM patients selected through systematic random sampling. Data collection involved a semi-structured questionnaire, Morisky Medication Adherence Scale-4 (MMAS-4), Diabetes Treatment Satisfaction Questionnaire (DTSQ), and Diabetes Distress Scale-17 (DDS-17). Statistical analysis was performed using Chi-square tests and multiple logistic regression in Statistical Package for Social Sciences (SPSS) version 25 with significance value at p<0.05. Results: The mean age of participants was 46.3±10.4 years. Majority of the participants were female 186 (53.1%). Most of the participants were married 340 (97.1%) and 220 (62.9%) were employed, and over 189 (54%) belonged to the upper-middle class as per the Modified BG Prasad Scale. Among the participants, 135 (38.6%) exhibited high adherence, 137 (39.1%) moderate adherence, and 78 (22.3%) low adherence. Moderate treatment satisfaction was observed in 278 (79.4%), and 126 (36%) reported clinically significant psychological distress. Bivariate analysis reported that medication adherence showed significant associations with age, educational status, occupation, Socioeconomic Status (SES), mode of drug intake, number of doses per day, family support, glycaemic control drug regimen (p-value <0.05). Medication adherence also showed significant associations with treatment satisfaction scale (p-value=0.0001) and DDS (p-value=0.022). Multiple logistic regression analysis showed significance for age (p-value=0.002), educational status (p-value=0.010) and mode of drug intake (p-value=0.008). Conclusion: Medication adherence among rural T2DM patients was moderate and influenced by treatment satisfaction and psychological distress. Strengthening education, enhancing psychological support and implementing community based interventions are critical in improving adherence and clinical outcomes.